Multiple patterns of diblock copolymer confined in irregular geometries with soft surface - 李颖 孙敏娜 张进军 潘俊星 郭宇琦 王宝凤 武海顺 (Chinese physics B, 2015)
The different confinement shapes can induce the formation of various interesting and novel morphologies, which might inspire potential applications of materials. In this paper, we study the directed self-assembly of diblock copolymer confined in irregular geometries with a soft surface by using self-consistent field theory. Two types of confinement geometries are considered, namely, one is the concave pore with one groove and the other is the concave pore with two grooves. We obtain more novel and different structures which could not be produced in other two-dimensional（2D） confinements. Comparing these new structures with those obtained in regular square confinement, we find that the range of ordered lamellae is enlarged and the range of disordered structure is narrowed down under the concave pore confinement.We also compare the different structures obtained under the two types of confinement geometries, the results show that the effect of confinement would increase, which might induce the diblock copolymer to form novel structures. We construct the phase diagram as a function of the fraction of B block and the ratio of h/L of the groove. The simulation reveals that the wetting effect of brushes and the shape of confinement geometries play important roles in determining the morphologies of the system. Our results improve the applications in the directed self-assembly of diblock copolymer for fabricating the irregular structures.